Targeted and reversible disruption of the blood-testis barrier by an FSH mutant-occludin peptide conjugate - Wong, Ching-Hang (2006)
The blood-testis barrier (BTB) is one of the tightest blood-tissue barriers in mammals. As such, it poses a challenge to deliver any drugs to the seminiferous epithelium of the testis, such as a nonhormonal male contraceptive. To circumvent this problem, a genetically engineered follicle-stimulating hormone (FSH) mutant protein was produced in Spodoptera furgiperda (Sf)-9 insect cells to serve as a testis-specific carrier. Subsequently, a 22-amino acid peptide corresponding to the second extracellular loop of occludin, which was known to disrupt BTB integrity in vivo, was inserted to the FSH mutant by polymerase chain reaction (PCR), as well as chemical cross-linking. This molecule was found to have negligible hormonal activity but was still capable of binding to FSH receptors, which are restricted to Sertoli cells in mammals. When this FSH mutant-occludin peptide conjugate was administered to adult rats at 40 µg/adult rat (~300 gm b.w.) via intraperitoneally (i.p.) injection, it induced transient and reversible disruption of the BTB, while at 150 µg/rat, it induced partial germ cell loss from the testis, particularly elongating/elongate spermatids. Most importantly, this effect was limited to the BTB without compromising the TJ-barrier integrity or cell adhesion in epithelia of other organs, such as kidney, liver, and small intestine. In summary, the use of an FSH mutant-occludin peptide conjugate is a feasible nanodevice to transiently compromise the BTB.—Wong, C.-H., Mruk, D. D., Lee, W. M., Cheng, C. Y. Targeted and reversible disruption of the blood-testis barrier by an FSH mutant-occludin peptide conjugate.